Nerves in the Tumor Microenvironment: Origin and Effects - Wang, Wenjun; Li, Lingyu; Chen, Naifei; Niu, Chao; Li, Zhi; Hu, Jifan; Cui, Jiuwei (Frontiers in Cell and Developmental Biology, 2020)
Several studies have reported the vital role of nerves in tumorigenesis and cancer progression. Nerves have been shown to infiltrate the tumor microenvironment thereby accelerating growth and dissemination of cancer. Perineural invasion, a process in which cancer cells invade the surrounding nerves, provides an alternative route for metastatic spread and generation of tumor-related pain. Recent studies suggest that the dysfunction of central and sympathetic nervous systems, and hormone network disorders which are induced by psychological stress may influence the malignant progression of cancer through multiple mechanisms. This reciprocal interaction between nerves and cancer cells provides novel insights into the cellular and molecular bases of tumorigenesis and points to the potential utility of anti-neurogenic therapies. This review focus on the evolving understanding of the cross-talk between nerves and cancer cells thus uncovering potential therapeutic targets for cancer patients.